Contemporary Trends in Global Mortality of Sepsis Among Young Infants Less Than 90 Days: A Systematic Review and Meta-Analysis - Gan, Ming Ying; Lee, Wen Li; Yap, Bei Jun; Seethor, Shu Ting Tammie; Greenberg, Rachel G.; Pek, Jen Heng; Tan, Bobby; Hornik, Christoph Paul Vincent; Lee, Jan Hau; Chong, Shu-Ling (Frontiers in Pediatrics, 2022)
Objective Current knowledge on the global burden of infant sepsis is limited to population-level data. We aimed to summarise global case fatality rates (CFRs) of young infants with sepsis, stratified by gross national income (GNI) status and patient-level risk factors. Methods We performed a systematic review and meta-analysis on CFRs among young infants <90 days with sepsis. We searched PubMed, Cochrane Central, Embase and Web of Science for studies published between January 2010 and September 2019. We obtained pooled CFRs estimates using the random effects model. We performed a univariate analysis at patient-level and a meta-regression to study the associations of gestational age, birth weight, onset of sepsis, GNI, age group and culture-proven sepsis with CFRs. Results The search yielded 6314 publications, of which 240 studies (N=437,796 patients) from 77 countries were included. Of 240 studies, 99 were conducted in high-income countries, 44 in upper-middle-income countries, 82 in lower-middle-income countries, 6 in low-income countries and 9 in multiple income-level countries. Overall pooled CFR was 18% (95% CI, 17%-19%). The CFR was highest for low-income countries [25% (95% CI, 7%-43%)], followed by lower-middle [25% (95% CI, 7%-43%)], upper-middle [21% (95% CI, 18%-24%)] and lowest for high-income countries [12% (95% CI, 11%-13%)]. Factors associated with high CFRs included prematurity, low birth weight, age less than 28 days, early onset sepsis, hospital acquired infections and sepsis in middle- and low-income countries. Study setting in middle-income countries was an independent predictor of high CFRs. We found a widening disparity in CFRs between countries of different GNI over time. Conclusions Young infant sepsis remains a major global health challenge. The widening disparity in young infant sepsis CFRs between GNI groups underscore the need to channel greater resources especially to the lower income regions. Trial registry This study is registered with PROSPERO (CRD42020164321).